Pencitraan Dan Pemrograman Berdasarkan Perhitungan Aplikasi Volume Paket Logistik - Dyna Ayunita; Dodi Sofyan Arief; Midriem Mirdanies (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The camera is a tool for capturing waves of light reflected by an object, so that the object can be mapped in the form of an image on an image digital camera whose result is an image in digital form. Image processing is done with a digital computer so the image to be processed first is transformed into discrete quantities of gray level values at the points of the image element. Generally digital images are rectangular which has a certain width and height, which is usually expressed in the number of points or pixels (picture element or pixel). Image size can also be expressed physically in units of length (for example mm or inch). The determination of volume in the optical grading system can be done using laser triangulation method and wide measurement of 2D imagery, after that using a computer algorithm to get the results of 3D images to determine the volume of objects. Optical grading methods usually use the camera to obtain 2D images (area width) or use the weight of the product to estimate the real volume. An algorithm that combines triangulation (2D) techniques and 2D measurements can be used to construct 3D surfaces so that they can measure the volume of a product. In this study MATLAB is ultilized for data processing to get the large of the object. Key Word : Camera, imaging, triangulation method, volume, MATLAB